2018
DOI: 10.2147/cmar.s174656
|View full text |Cite
|
Sign up to set email alerts
|

A cumulative score based on preoperative fibrinogen and the neutrophil–lymphocyte ratio to predict outcomes in resectable gastric cancer

Abstract: BackgroundRecent studies have revealed that preoperative fibrinogen and the neutrophil–lymphocyte ratio (NLR) are associated with poor outcome in gastric cancer (GC). We aimed to evaluate whether the fibrinogen and the NLR score had a consistent prognostic value for resectable GC.MethodsWe analyzed 1,293 consecutive patients who underwent curative surgery for GC. The F-NLR score was 2 for patients with hyperfibrinogenemia (>400 mg/dL) and elevated NLR (≥5.0), 1 for those with one abnormal index, and 0 for thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
(42 reference statements)
3
21
0
Order By: Relevance
“…Data on the following clinicopathological characteristics were collected from medical records: sex, age, primary tumour location, differentiation, tumour size, and TNM stage. Similar to other studies [12][13][14], blood samples were obtained within 1 week before surgery for the measurement of neutrophil, lymphocyte, monocyte, platelet, albumin (Alb), and fibrinogen (Fib) levels. Patients meeting any of the following criteria were excluded: (1) histologically confirmed stage IV disease, (2) severe complications or death within 15 days after diagnosis, (3) incomplete pretreatment laboratory parameters, (4) malignancies other than gastric cancer, (5) haematological disorders which could potentially affect the white blood cells, and (6) evidence of any autoimmune or infectious diseases or liver dysfunction indicated by abnormal alanine aminotransferase.…”
Section: Patients and Follow-upmentioning
confidence: 99%
“…Data on the following clinicopathological characteristics were collected from medical records: sex, age, primary tumour location, differentiation, tumour size, and TNM stage. Similar to other studies [12][13][14], blood samples were obtained within 1 week before surgery for the measurement of neutrophil, lymphocyte, monocyte, platelet, albumin (Alb), and fibrinogen (Fib) levels. Patients meeting any of the following criteria were excluded: (1) histologically confirmed stage IV disease, (2) severe complications or death within 15 days after diagnosis, (3) incomplete pretreatment laboratory parameters, (4) malignancies other than gastric cancer, (5) haematological disorders which could potentially affect the white blood cells, and (6) evidence of any autoimmune or infectious diseases or liver dysfunction indicated by abnormal alanine aminotransferase.…”
Section: Patients and Follow-upmentioning
confidence: 99%
“…Elevated fibrinogen levels are associated with poor outcomes in gynaecological cancer (23), lung cancer (24) and BC (25). Previous studies using a scoring system based on the combination of fibrinogen concentration and neutrophil-to-lymphocyte ratio (F-NLR) have reported that a high F-NLR score is associated with poor outcomes in different types of cancer (26)(27)(28)(29). However, to the best of our knowledge, the prognostic value of F-NLR in BC remains unknown.…”
Section: Combination Of Preoperative Fibrinogen Concentration and Neumentioning
confidence: 99%
“…Previous studies have shown that increased plasma fibrinogen indicates poor prognosis of various cancers including GC. 4,5 Malnutrition is a common clinical manifestation of gastrointestinal cancers and is also a prognostic indicator of cancer. Albumin is commonly used to assess nutritional status, and hypoalbuminemia is associated with poor prognosis in several cancers such as lung, gastric, and colon cancers.…”
Section: Introductionmentioning
confidence: 99%